Q-switched Erbium-doped Fiber Laser with a Black Phosphorus Saturable Absorber - Razak, Nurul Nadia; Abdul Latiff, Anas; Zakaria, Zahriladha; Harun, Sulaiman Wadi (Photonics Letters of Poland, 2017)
A passively Q-switched Erbium-doped fiber laser (EDFL) is demonstrated using a black phosphorus saturable absorber as the Q-switcher. The laser generates a stable pulse operating at a wavelength of 1562.35 nm within a pump power region from 7.2 mW to 42.3 mW. At 980 nm pump power of 42.3 mW, the EDFL generates an optical pulse train with a repetition rate of 44.72 kHz and pulse width of 9.8 us. The maximum pulse energy of 81.5 nJ is obtained at a pump power of 35.2 mW. A higher performance Q-switched EDFL is expected to be achieved with the optimization of the saturable absorber and laser cavity. Full Text: PDF References R. Mas-Balleste, C. Gomez-Navarro, J. Gomez-Herrero and F. Zamora, "2D materials: to graphene and beyond", Nanoscale 3, 20 (2011). CrossRef Z. Sun, T. Hasan, F. Torrisi, D. Popa, G. Privitera, F. Wang, F. Bonaccorso, D. M. Basko and A. C. Ferrari, "Graphene Mode-Locked Ultrafast Laser", ACS nano 4, 803 (2010) CrossRef F. Xia, H. Wang and Y. Jia, "Rediscovering black phosphorus as an anisotropic layered material for optoelectronics and electronics.", Nat Commun 5 (2014). CrossRef G. Sobon, "Mode-locking of fiber lasers using novel two-dimensional nanomaterials: graphene and topological insulators [Invited]", Photonics Research 3, A56 (2015). CrossRef Y. Chen, G. Jiang, S. Chen, Z. Guo, X. Yu, C. Zhao, H. Zhang, Q. Bao, S. Wen and D. Tang, "Mechanically exfoliated black phosphorus as a new saturable absorber for both Q-switching and Mode-locking laser operation", Optics express 23, 12823 (2015). CrossRef M. Hisyam, M. Rusdi, A. Latiff and S. Harun, "Generation of Mode-Locked Ytterbium Doped Fiber Ring Laser Using Few-Layer Black Phosphorus as a Saturable Absorber", IEEE Journal of Selected Topics in Quantum Electronics 23, 39 (2017). CrossRef S. Sugai and I. Shirotani, "Raman and infrared reflection spectroscopy in black phosphorus", Solid state communications 53, 753 (1985). CrossRef Z.-C. Luo, M. Liu, Z.-N. Guo, X.-F. Jiang, A.-P. Luo, C.-J. Zhao, X.-F. Yu, W.-C. Xu and H. Zhang, "Microfiber-based few-layer black phosphorus saturable absorber for ultra-fast fiber laser", Optics express 23, 20030 (2015). CrossRef A. Latiff, M. Rusdi, M. Hisyam, H. Ahmad and S. Harun, "A generation of 2 um Q-switched thulium-doped fibre laser based on anatase titanium(IV) oxide film saturable absorber", Journal of Modern Optics 64, 187 (2017). CrossRef J. Bogusławski, G. Soboń, K. Tarnowski, R. Zybała, K. Mars, A. Mikuła, K. M. Abramski and J. Sotor, "All-polarization-maintaining-fiber laser Q-switched by evanescent field interaction with Sb2Te3 saturable absorber", Optical Engineering 55, 081316 (2016). CrossRef Z. Wang, Y. Xu, S. C. Dhanabalan, J. Sophia, C. Zhao, C. Xu, Y. Xiang, J. Li, and H. Zhang, "Black Phosphorus Quantum Dots as an Efficient Saturable Absorber for Bound Soliton Operation in an Erbium Doped Fiber Laser," IEEE Photonics Journal 8, 1 (2016). CrossRef